The maternal knowledge and occupation concerning the development of baby - Devi Elfita Sari; Ria Gustirini (International Journal of Health Science and Technology, 2019)
Child development towards critical times needed or stimulation that is useful for developing potential so that it is necessary to have more attention and needs of children at various stages of development. Knowing the correlation between maternal knowledge and occupation toward baby's developmental milestones. Analytical survey research with cross sectional approach, the populations of this study were all babies aged 0-5 years. The number of samples of this study were 48 respondents where sampling was taken by purposive sampling technique with inclusion criteria. Analyzed using univariate and bivariate analysis. The results of the study showed that a small proportion of children with abnormal development 16 respondents (33.3%), respondents with less knowledge 20 respondents (41.7%) and respondents who worked 18 respondents (37.5%). Based on statistical test Chi-square, there was a significant correlation between maternal knowledge and occupation toward baby’s developmental milestones (p value 0.003) and obtained that there was correlation between maternal occupation and baby’s developmental milestones (p value 0.004). Conclusion: It was concluded that there was a significant correlation between maternal knowledge and occupation toward baby’s developmental milestones.